Decreased Treg Cell and TCR Expansion Are Involved in Long-Lasting Graves’ Disease - Chen, Ziyi; Liu, Yufeng; Hu, Shiqian; Zhang, Meng; Shi, Bingyin; Wang, Yue (Frontiers in Endocrinology, 2021)
Graves’ disease (GD) is a T cell-mediated organ-specific autoimmune disorder. GD patients who have taken anti-thyroid drugs (ATDs) for more than 5 years with positive anti-thyroid stimulating hormone receptor autoantibodies value were defined as persistent GD (pGD). To develop novel immunotherapies for pGD, we investigated the role of T cells in the long-lasting phase of GD. Clinical characteristics were compared between the pGD and newly diagnosed GD (nGD) (N=20 respectively). Flow cytometric analysis was utilized to determine the proportions of Treg and Th17 cells (pGD, N=12; nGD, N=14). T cell receptor sequencing (TCR-seq) and RNA sequencing (RNA-seq) were also performed (pGD, N=13; nGD, N=20). Flow cytometric analysis identified lower proportions of Th17 and Treg cells in pGD than in nGD (P=0.0306 and P=0.0223). TCR-seq analysis revealed a lower diversity (P=0.0025) in pGD. Specifically, marked clonal expansion, represented by an increased percentage of top V-J recombination, was observed in pGD patients. Interestingly, pGD patients showed more public T cell clonotypes than nGD patients (2741 versus 966). Meanwhile, RNA-seq analysis revealed upregulation of the inflammation and chemotaxis pathways in pGD. Specifically, the expression of pro-inflammatory and chemotactic genes (IL1B, IL13, IL8 and CCL4) was increased in pGD, whereas Th17 and Treg cells associated genes (RORC, CARD9, STAT5A and SATB1) decreased in pGD. Additionally, TCR diversity was negatively correlated with the expression of pro-inflammatory or chemotactic genes (FASLG, IL18R1, CCL24 and CCL14). These results indicated that Treg dysregulation and the expansion of pathogenic T cell clones might be involved in the long-lasting phase of GD via up-regulating chemotaxis or inflammation response. To improve the treatment of pGD patients, ATDs combined therapies, especially those aimed at improving Treg cell frequencies or targeting specific expanded pathogenic TCR clones, are worth exploring in the future.